Review: a call to galvanize a movement to end the oppression of women worldwide - White, Deborah (Social justice, 2011)
The article reviews the book "Half the Sky: Turning Oppression Into Opportunity for Women Worldwide" by Nicholas Kristof and Sheryl WuDunn.